Effect of fetal hemoglobin on microvascular regulation in sickle transgenic-knockout mice - Kaul, Dhananjay K. (American Society for Clinical Investigation, 2004)
In sickle cell disease, intravascular sickling and attendant flow abnormalities underlie the chronic inflammation and vascular endothelial abnormalities. However, the relationship between sickling and vascular tone is not well understood. We hypothesized that sickling-induced vaso-occlusive events and attendant oxidative stress will affect microvascular regulatory mechanisms. In the present studies, we have examined whether microvascular abnormalities expressed in sickle transgenic-knockout Berkeley (BERK) mice (which express exclusively human α- and β(S)-globins with <1% γ-globin levels) are amenable to correction with increased levels of antisickling fetal hemoglobin (HbF). In BERK mice, sickling, increased oxidative stress, and hemolytic anemia are accompanied by vasodilation, compensatory increases in eNOS and COX-2, and attenuated vascular responses to NO-mediated vasoactive stimuli and norepinephrine. The hypotension and vasodilation (required for adequate oxygen delivery in the face of chronic anemia) are mediated by non-NO vasodilators (i.e., prostacyclin) as evidenced by induction of COX-2. In BERK mice, the resistance to NO-mediated vasodilators is associated with increased oxidative stress and hemolytic rate, and in BERK + γ mice (expressing 20% HbF), an improved response to these stimuli is associated with reduced oxidative stress and hemolytic rate. Furthermore, BERK + γ mice show normalization of vessel diameters, and eNOS and COX-2 expression. These results demonstrate a strong relationship between sickling and microvascular function in sickle cell disease.